Comparison of online greenhouse gas accounting tools for agriculture - MacSween, Kirsten; Feliciano, Diana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Key messages ◼ Six online greenhouse gas (GHG) accounting tools were identified and analyzed to determine their advantages and disadvantages to how they estimate GHG emissions and emission reductions and provide context-relevant mitigation options with details regarding mitigation potential and potential trade-offs. ◼ The tools are the CCAFS Mitigation Options Tool (CCAFS-MOT), the Agriculture and Land Use Greenhouse Gas Inventory (ALU) Software, the Small-Holder Agriculture Monitoring and Baseline Assessment (SHAMBA), the EX-Ante Carbon-balance Tool (EX-ACT), the Cool Farm Tool (CFT), and the Carbon Benefits Project (CBP). ◼ This comparison aims to help potential users to better understand in which projects and activities the GHG accounting tools will be most relevant. ◼ Differential features include data required, emission factors used, whether mitigation options are identified, and usability at different geographic scales.